REBRANDING KEBUN BINATANG SURABAYA DENGAN MENGGUNAKAN KARAKTERISTIK BERBASIS BUDAYA LOKAL - Andriani, Dewi Restya; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: The goal of the rebranding of Surabaya Zoo is to preserve the local culture. Research conducted using qualitative research methods, namely by doing interviews, observation, documentation, library and study to get the data used as the supporter of the creation of the concept design of rebranding. The data were analyzed by using multiple stages, namely the reduction of the data, the presentation of data and conclusions. rom the analysis of the data found few keyword refers to the communication strategy rebranding which will be used to achieve the intended targets of the audians. After analysis of the data, the concept of virtue or keyword design of rebranding of